Incidence of falls in a cohort of critical adults: a cause for concerns? - Andréia Martins Specht; Gabriele Peres de Sousa; Mariur Gomes Beghetto (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To describe the incidence and to report the cases of falls in a cohort of critical adults. Method: A prospective cohort study, conducted in 2018 at an adult Intensive Care Unit (ICU) in the south of Brazil. The patients were followed up from admission to discharge; observations were made in the morning and afternoon. The clinical and care variables were evaluated. The descriptive analysis was performed followed by the reporting of the cases. Results: 551 patients were monitored during 6 [3-12.7] days of hospitalization, generating 7,839 observations. There were four cases of falls, with an incidence rate of 5.1/10.000 observations/day - confidence interval of 99% [0.9 to 16] and density of incidence of 7/10.000 observations/day - confidence interval of 99% [1.2 to 22]. No serious harms were observed. Conclusion: Falls occur less in the ICU, which can be explained by the use of safe care practices.